The correlation between students' information literacy and the utilisation of AI text generator in completing academic studies - Muhaemin; Lusiana, Elnovani; Khadijah, Ute Lies Siti Khadijah (Record and Library Journal, 2024)
Background of the study: The use of AI Text Generator (ATG) provides many conveniences for students, especially in accessing information in the form of text to make research proposals as a requirement for completing academic studies in lectures, but on the other hand the use of this technology also has a negative impact if not used wisely. Purpose: To describe the correlation between student information literacy and the utilisation of AI Text Generator in completing academic studies Method: Simple correlation to determine the level or degree of correlation between two variables. Findings: There is a significant correlation between students' information literacy and its five indicators with the utilization of AI Text Generator in completing academic studies. The level of correlation is in the moderate category. The types of AI Text Generator most widely used by students are ChatGPT, Perplexity, and followed by several other types of ATG. The reasons students use ATGs include developing ideas and information, efficiency, writing assistance, concept development, reference, problem solving, and improving the quality of writing. Conclusion: The existence of a correlation with a level of correlation strength that is in the moderate category indicates that these two variables influence each other but are not completely dependent on each other.